Analisis Pengaruh Fraksi Bijih Massive Silica dari Uji Pulverized Bottle Roll Test - Muhammad Selgy Rio Auzza Maisano Saifudin; Solihin; Linda Pulungan (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Copper which has many benefits in everyday life makes people look for several methods to extract copper in accordance with the intent and purpose of its use, the purpose of this test is to determine the % recovery value of the ore characteristic of massive silica by using fine ore leaching and considering the variation of the ore fraction used. In determining the % recovery of the ore to be tested, the sizes are 100#, 150# and 200# with a NaCN concentration of 500 ppm. Apart from the ore fraction and NaCN concentration, the leaching time will also be determined for 48 hours using a PBRT (Pulverized Bottle Roll Test). Samples taken are in the form of a solution which will be analyzed for Cu levels using an AAS (Atomic Absorption Spectrometer). Based on the results obtained in this test when viewed from the time used in sampling, the optimum % recovery is obtained at 24 – 48 hours when viewed from the ore fraction parameters used in this test, for Massive Silica rocks the highest % copper recovery is 54.1% with leaching time of 48 hours at 100# fraction and 500 ppm NaCN concentration. Abstrak. Tembaga yang memiliki manfaat yang banyak dalam kehidupan sehari-hari menjadikan manusia mencari beberapa metode untuk mengekstrak tembaga sesuai dengan maksud dan tujuan penggunaannya, tujuan dari pengujian ini untuk mengetahui nilai % recovery dari bijih karakteristik massive silica dengan menggunakan pelindian bijih halus dan mempertimbangkan variasi dari fraksi bijih yang digunakan. Dalam menentukan % recovery dari bijih yang akan di uji ukuran yaitu 100#, 150# dan 200# dengan konsentrasi NaCN 500 ppm. Selain dari fraksi bijih dan konsentrasi NaCN, waktu pelindian juga juga akan ditetapkan selama 48 jam dengan menggunakan PBRT (Pulverized Bottle Roll Test), sampel yang diambil berbentuk solution yang akan di lakukan analisis terhadap kadar Cu dengan menggunakan alat AAS (Atomic Absorption Spectrometer). Berdasarkan hasil yang didapat dalam pengujian ini jika dilihat dari waktu yang digunakan dalam pengambilan sampel maka % recovery yang optimum didapat pada waktu 24 – 48 jam jika dilihat dari parameter fraksi bijih yang digunakan dalam pengujian ini, untuk batuan Massive Silica % recovery tembaga yang terbesar yaitu 54,1% dengan waktu pelindian 48 jam pada fraksi 100# dan konsentrasi NaCN 500 ppm.